Revisiting Short-term Outcomes of Conventional and Computer-Assisted Total Knee Arthroplasty: A Population-based Study. (10th June 2022) - Ahmed, Abdalrahman G.; Tian, Yao; Hasan, Mohamed; Harris, Alexandra; Ghomrawi, Hassan M. K.
Abstract : Background: Population-based studies showing the advantage of computer-assisted total knee arthroplasty (CATKA) over conventional total knee arthroplasty (TKA) are outdated. More recent institution-based studies with relatively small sample sizes may hinder wider adoption. This cohort-based study aimed to compare postoperative CATKA and TKA in-hospital complications and 90-day all-cause readmissions using 2017-2018 data. Methods: Patients who underwent a primary unilateral CATKA or TKA were identified in the New York Statewide Planning and Research Cooperative System database. In-hospital complications were defined based on the 2020 Centers for Medicare & Medicaid Services total hip arthroplasty and TKA complications measure. Ninety-day readmissions were identified using unique patient identifiers. Logistic regression with a generalized estimating equation was used to assess associations of computer assistance with in-hospital complications and 90-day all-cause readmissions. Results: A total of 80, 468 TKAs were identified during the study period, of which 7, 395 (9.2%) were CATKAs. Significantly fewer complications occurred among patients who had CATKAs compared with conventional TKAs (0.4% of total CATKAs vs 2.6% of total conventional TKAs, P < 0.001); patients who had CATKAs had fewer 90-day all-cause readmissions compared with those who underwent TKAs (363 vs 4, 169 revisits, P < 0.01). Computer assistance was associated with significantly lower odds of in-hospital complications (odds ratio, 0.15, 95% confidence interval, 0.09 to 0.24; P < 0.05) but not 90-day all-cause readmissions. Conclusion: Patients undergoing CATKAs had markedly lower odds of in-hospital complications, compared with patients having TKAs, which has implications for both patient outcomes and hospital reimbursement. These more recent cohort-based findings encourage wider CATKA adoption.